Dance in the “Encyclopedia of Artistic Terminologyˮ: Reflections on the GAKhN Choreology Project - Sirotkina, Irina (Wiener Slawistischer Almanach, 2026)
The First (Philosophical) Volume of the Encyclopedia of Artistic Terminology was to include entries on dance, ballet, choreography, choreology and gesture. Although the texts are not known and it is not clear whether the entries were ever written, the decision to include them is telling. It signals that, from the very beginning of the State Academy of Artistic Sciences (GAKhN), dance assumed an important place in the institution. Wassily Kandinsky famously included movement in his synthetic art project, giving an impulse to the establishment of dance studies at the Academy. Throughout the 1920s, the Choreological Laboratory ran a substantial research programme. The article provides a brief overview of dance studies at GAKhN and discusses the place of dance in the Encyclopedia of Artistic Terminology.